The Efficacy of Intramuscular Benzathine Penicillin for Preventing Recurrent Cellulitis: A Nationwide Population-Based Study. (4th October 2017) - Lin, Szu-Han; Lee, Yu-Lin; Chen, Yen-Yu; Yeh, Yi-Chun; Liu, Chun-Eng
Abstract: Background: Recurrent cellulitis is a vexing clinical problem with huge financial burden on healthcare resources. Though intramuscular antibiotics had been suggested as a prevention strategy but the evidence is scarce. Methods: We conducted a cohort study by using Taiwan's National Health Insurance Research Database (NHIRD) between 2000 and 2008. Patients received intramuscular benzathine pencillin 2.4 MU every 4 weeks at least three prescriptions within half a year were enrolled and followed for 1 year since the first dose. The prevention efficacy was determined by comparing the incidence of recurrent cellulitis in the prophylactic period to non-prophylactic period in each enrolled subject by a Poisson regression model. The prophylactic period was defined as 4 weeks after the date of each dose of benzathine penicillin injection and non-prophylactic period was the time not covered by penicillin during the follow-up period. Results: In total, 211 patients were enrolled, including 123(58.3%) men. An average of 7.9 doses of IM benzathine penicillin was given in the study period. The incidence rate of recurrent cellulitis in the prophylactic period was 0.31 episode/patient-year, significantly lower than that of 0.77 episodes/patient-year in the non-prophylactic period ( P = 0.004). The common underlying diseases of enrolled patients included diabetes mellitus (73, 35.4%), tinea pedis (69, 33.5%), impaired venous drainage (20, 9.7%), joint replacement of lower extremity (13, 6.3%) and edema status including congestive heart failure (19, 9.2%), chronic renal failure (15, 7.3%), and cirrhosis (8, 3.9%). In multivariate analysis of Poisson regression model, penicillin prophylaxis was associated with lower recurrence (relative risk (RR), 0.30; 95% confidence interval (CI), 0.13–0.69, P = 0.005), in contrast, impaired venous drainage (RR 2.78; CI, 1.20–6.48, P = 0.018) and tinea pedis (RR 3.04; CI, 1.17–7.90, P = 0.022) were associated with higher risk of recurrence. Conclusion: The study was the largest cohort that demonstrated intramuscular injection of 2.4 million units benzathine penicillin with 4-week interval significantly reduced the incidence of recurrent cellulitis. Disclosures: All authors: No reported disclosures.